A dual function nanocrystalline TiO2 platform for solar photocatalysis and self cleaning application. (October 2017) - Naufal, Binu; Ullattil, Sanjay Gopal; Periyat, Pradeepan
Graphical abstract: Highlights: Nanocrystalline TiO2 and Sm 3+ doped TiO2 were synthesised by a modified sol-gel synthetic strategy. TiO2 nanocrystals without Sm 3+ have shown oxygen richness, while implementing Sm 3+ incorporation, oxygen deficiency was induced along with a significant enhancement in the overall photocatalytic activity. The photocatalytic activities of TiO2 and Sm 3+ doped TiO2 at various calcination temperatures were investigated by the degradation of methylene blue solution under UV and visible light. Photocatalytic study showed that the Sm 3+ doped TiO2 nanostructure calcined at 500 °C with higher defects at the nanosurface, has the highest photoactivity. Self-cleaning coatings on glass bottles were developed using these photocatalysts. Abstract: Nanocrystalline anatase TiO2 and Sm 3+ doped TiO2 having defective and non-defective nature were synthesised and systematically examined as photocatalysts with a function of dopant present (1, 2, 5 and 10 wt%) and temperature at 300, 500 and 700 °C using methylene blue dye as model system. A bare TiO2 nanocrystal has shown oxygen richness and while incorporating Sm 3+, oxygen deficiency was induced along with a significant enhancement in the overall photocatalytic activity. Photocatalytic study showed that the Sm 3+ doped TiO2 nanostructure calcined at 500 °C with higher defects at the nanosurface has the highest activity under both UV and sunlight irradiation. Finally a dual function nano TiO2 platform were demonstrated using Sm 3+ doped TiO2 sol coated self-cleaning glass bottle.